Synergistic defecation effects of Bifidobacterium animalis subsp. lactis BL-99 and fructooligosaccharide by modulating gut microbiota - Zhang, Qi; Zhao, Wen; Luo, Jie; Shi, Shaoqi; Niu, Xiaokang; He, Jian; Wang, Yicheng; Zeng, Zhaozhong; Jiang, Qiuyue; Fang, Bing; Chen, Juan; Li, Yixuan; et al. (Frontiers in Immunology, 2025)
IntroductionSynbiotics have revealed the possibility of improving constipation through gut microbiota. The synergistic efficacy of Bifidobacterium animalis subsp. lactis BL-99 (BL-99) and fructooligosaccharide (FOS) on constipation have not been investigated.MethodsLoperamide-induced constipated mice model was established to explore the effect of BL-99, FOS, and BL-99+FOS on changes of defecation-related parameters, gut microbiota and metabolites.Results and discussionThe results showed that BL-99, FOS, and BL-99+FOS each alleviated constipation, with the synbiotic showing significant efficacy in the first black stool defecation time, fecal number, fecal weight, and the gastrointestinal transit rate (P < 0.05). Additionally, significant increased in serum 5-HT and IL-10 were observed in the BL-99+FOS group, alongside an increased relative abundance of Lachnospiraceae_NK4A136_group, Blautia, and Clostridium sensu stricto 1, while significantly reducing the relative abundance of Alistipes and Bacteroides. These changes facilitated alterations in short-chain fatty acids (SCFAs) metabolism, and were closely associated with the expression of genes related to the 5-HT pathway and the modulation of serum inflammatory factors. This study provides a theoretical basis for BL-99 and FOS synbiotics to improve constipation by regulating the gut microbiota and metabolites.